Analysis Of Plyometric Training In Basketball: Systematic Literatur Review - Faradz Jiddan; Adi S (Universitas Negeri Semarang, 2025)
Study purpose the reason for this study is to look at the Analysis of the Use of Plyometric Training in Basketball. Materials and methods PRISMA tables will be used for systematic review and meta- analysis in this review investigation. Various studies published from January 2020 to Desember 2024. In the search procedure, the following keywords were used: (1) Plyometric; (2) Training; (3) Basketball. The search in this study used the Scopus research journal database. Results the theme of this research as a whole obtained 153 articles. Consisting of 57 articles,10 relevant articles were retrieved. Conclusions analysis of plyometric training in basketball includes the effect of plyometric training based on the results of relevant research, including strengthening leg muscle explosiveness, movement flexibility, maximizing vertical jump, stabilizing hanging time, improving performance (jump shoot, rebound, lay up) and minimizing the risk of injury. However, further research is needed with adjustments to the characteristics of athletes.